Structure, morphology, thermal and electrochemical studies of electrochemically synthesized polyaniline/copper oxide nanocomposite for energy storage devices. (21st February 2020) - Ashokkumar, S P; Yesappa, L; Vijeth, H; Niranjana, M; Vandana, M; Devendrappa, H
Abstract: Polyaniline (PANI)/copper oxide nano composite (PCN) was synthesized by electrochemical deposition method. The PCN nanocomposite was characterized by using Fourier transform infra-red (FT-IR) spectroscopy, x-ray diffraction (XRD), UV-Visible absorption spectroscopy, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Impedance analyser and electrochemical workstation methods. The FT-IR analysis shows proper chemical interaction of PANI with CuO nanoparticles. In XRD it is found that the amorphousity increases with increasing CuO concentration. The surface morphology observed changes from granular to rod shape structure and TEM gives the particle size range from 30–70 nm. UV-visible spectra shows increase the absorption and decreased the optical band gap with addition of nano composite concentration. The CV curve exhibits rectangular shape with high current density and specific capacitance (Csp ) was observed increases with increasing CuO nano concentration at various scan rates from 100–500 mVs −1 . The highest specific capacitance (Csp ) value 286.66 Fg −1 was obtained for PCN1 nano composite. These results suggest that the PCN nano composite can be used in the energy storage device applications.